Erosion Losses from Banana-Pineapple Intercropping and Soil Loss Prediction Using Rusle - Abbasi, Mohammad Almas (1998)
Soil erosion in agricultural upland conditions was investigated in Puchong Farm, UPM from an intercropping system of banana-pineapple. To study the effectiveness of this intercropping system four erosion plots of same length but different width were prepared on a 9% slope. One plot was planted with banana crop, second with pineapple and third with intercrop of banana and pineapple, whereas one plot was kept as bare with regular cultivation every fortnight. All the plots were kept in weed-free condition. Each plot was equipped with sediment tanks, for the collection of soil loss and runoff from the plots. Measurement of soil loss and runoff was made after every erosive rainfall. The sediments and runoff water were analyzed for major nutrients after every growth period. The data indicate that the site soil is very susceptible to erosion. The highest soil loss during the nine months period was obtained from bare plot (105.5 mt/ha) followed by banana plot (40.6 mt/ha) whereas total soil loss from intercrop and pineapple plots were 26.5 and 25.0 mt/ha respectively. Total runoff from bare, banana, intercrop and pineapple were 11.1 x l06, 9.3xl06, 6.3xl06 and 7.2xl06 L/ha respectively. These came as a result of total rainfall of 2020 mm which was about 25% higher than the average of 10 previous years. Comparison of soil loss and runoff in different growth periods showed that, in the early growth period when the canopy cover was around 1 5%, soil loss and runoff were not significantly different among the plots. But after the establishment of crop canopy and root network, soil loss and run off were reduced significantly as compared to bare plot. The relationship of EI30 index with soil loss and runoff and the relationship of soil loss with runoff were significant at 1 % probability level for all the plots. The analysis of fertility status showed that at the top of the slope there was decrease in the fertility except for K in intercrop and C, N, P and K for pineapple as compared to the center and bottom of the slope for every plot.